Exploring the Overrepresentation of Black Male Students in Special Education: Causes and Recommendations - Delahunty, Michael; Chiu, Calli Lewis (Journal of Gender and Power, 2021)
An overrepresentation of Black male students identified as having disabilities is pervasive in American schools. This troubling reality may be the result of disconnects between Black males and their White teachers. Racial differences likely contribute to the high number of Black males referred for programs for students with disabilities. This paper explores the overrepresentation of Black male students identified as having disabilities and recommendations for supporting their success.